2018
DOI: 10.21548/40-1-2885
|View full text |Cite
|
Sign up to set email alerts
|

Gentisic Acid, Salicylic Acid, Total Phenolic Content and Cholinesterase Inhibitory Activities of Red Wines Made from Various Grape Varieties

Abstract: Alzheimer's disease is characterised by a decrease in acetylcholine (ACh) levels in the brain due to the activity of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). As a result, disorders in cholinergic transmission are observed, leading to cognitive impairment. In this work, the inhibition of AChE and BChE activities by red wines made of various grape varieties was determined for the first time. There was no significant difference in the polyphenol content between the grape varieties; neverthele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Extracts from natural products have shown that anti-cholinesterase activity has been associated with the phenolic compounds [13,14,43,44]. The few studies on the cholinesterases inhibition of wine and winemaking byproducts indicate that this activity is related to the type and structure of phenolic compounds [9,26]. In this study, the AChE than BChE inhibition observed for all the extracts from all types of winemaking byproducts is in accordance with previous results [9].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Extracts from natural products have shown that anti-cholinesterase activity has been associated with the phenolic compounds [13,14,43,44]. The few studies on the cholinesterases inhibition of wine and winemaking byproducts indicate that this activity is related to the type and structure of phenolic compounds [9,26]. In this study, the AChE than BChE inhibition observed for all the extracts from all types of winemaking byproducts is in accordance with previous results [9].…”
Section: Discussionsupporting
confidence: 92%
“…Although in vitro antioxidant activity of winemaking byproducts has been widely studied by different spectrophotometric methods, studies on the in vitro anti-cholinesterase properties of these products are still scarce. The recent studies on the cholinesterase inhibitory activities of red wine and seeds, skins and flesh from Vitis vinifera fruits can be highlighted [9,26]. These studies indicated that wine, seeds and skins had high anticholinergic activity.…”
Section: Introductionmentioning
confidence: 99%
“…All the wines showed very low values for residue malic acid (<0.01 g/L in most wines), meaning that they all underwent malolactic fermentation. It is interesting to note that in all three vintages certain parameters, like ethanol content and TPC, had different values to the typical averages and/or ranges for monovarietal Pinot noir wines from other European terroirs (Pedri et al, 2019;Stój et al, 2019;Van Leeuw et al, 2014). In fact, results reported in this work indicate higher average values for TPC (2224 ± 497 in 2016, 2663 ± 613 in 2017, 2444 ± 507 in 2018), ethanol content (13.36 ± 0.50 in 2016, 13.24 ± 0.50 in 2017, 13.64 ± 0.59 in 2018) and total titrable acidity (5.10 ± 0.46 in 2016, 5.37 ± 0.40 in 2017, 5.31 ± 0.48 in 2018).…”
Section: Standard Wine Analysis and Scoresmentioning
confidence: 89%
“…Studies have shown that a variety of phenolic acids, including hydroquinone, 4‐hydrobenzoic acid, 3,5‐dihydrobenzoic acid, caffeic acid, vanillic acid and chlorogenic acid, have the functions of inhibiting AChE and resisting oxidation. They can act as an inhibitor of AChE and BChE, and also inhibit the formation of amyloid β‐peptide fibrils (Isik & Beydemir, 2021; Ojo et al, 2018; Stoj et al, 2019).…”
Section: Anti‐ad Active Ingredients In Plantsmentioning
confidence: 99%